Sticky Information and Price Controls: Evidence from a Natural Experiment - Doron Sayag; Avichai Snir; Daniel Levy (SSRN, 2025)
We test the predictions of the sticky information model using a survey dataset by comparing the shoppers' accuracy in recalling the prices of regulated and comparable unregulated products. Regulated product prices change less frequently, vary less across stores and between brands, and are sold more than comparable but unregulated product prices. Therefore, shoppers would be expected to recall the regulated product prices more accurately. However, we find that shoppers are better at recalling the prices of unregulated products, in line with the sticky information model which predicts that shoppers will be more attentive to prices that change more frequently.
Keywords: D12; D83; D91; E31; K20; L11; L16; L50; 330; Sticky Information; Cost and Benefit of Information; Information Gathering; Information Processing; Price Cap; Price Regulation; Price Controls; Price Adjustment; Sticky Prices; Rigid Prices; Price Stickiness; Price Rigidity